Kerjasama Customs Indonesia-Malaysia dalam Menanggulangi Penyelundupan Pakaian Bekas ke Indonesia - Ria Ariesti Br Sitepu; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Eventhough the Minister of Trade Regulation Number 51/M-DAG/PER/7/2015 has beenestablished, the rampant of smuggling on secondhand ballpress clothing still occurs.Smuggiling of ballpress secondhand clothing is banned in Indonesia because it impacts onIndonesia's economy and well-being of its society.The majority of smuggling of ballpresssecondhand clothing comes from Malaysia. That is why, the cooperation between DJBCand the Royal JKDM is important to handle this phenomenon. The method of this researchis a qualitative research, that explains about the actions between DJBC and JKDM.Futhermore, these actions are being analyzed to find the factors of smuggiling of ballpresssecondhand clothing that currently is still happening. To answer this issue is by usingInternational Cooperation Theory and Institutional Liberalism. Finally it has found that thecooperation between DJBC and JKDM not maximal on handling smuggling of ballpresssecondhand clothing in Indonesia. Between Indonesia and Malaysia have differentviewpoints and interests on secondhand clothing. Eventhough, the DJBC and JKDM stillupholds within ASEAN Agreement on Customs that leads both countries on exchanginginformation and also to bind their cooperation that is called,